Reflective portfolio as an instrument of evaluation and self-evaluation in the teaching-learning process: Experience of the stricto sensu, graduate program of the master's degree in nursing at Pará State University and Federal University of Amazonas (Research, Society and Development, 2021)
Objective: to describe the experience of professors and students of the Master's Degree in Nursing at the University of the State of Pará, associated with the Federal University of Amazonas in the use of the reflective portfolio as an instrument of assessment and self-assessment in the teaching-learning process. Method: It deals with an experience report, using participatory observation regarding the use of active methodologies in the construction of the teaching of the subject “Nursing Technologies for education and health care”, from the 4th of August to the 27th of October 2020. Result: in this teaching-learning process, using active teaching methodologies and formative assessment, through the reflective portfolio, teachers played a fundamental role, acting as facilitators, emphasizing self-directed and student-centered learning. Such experiences brought as relevance to the actors involved (teachers, students and managers), the possibility of seeing teaching as a privileged space, in which it is noticeable the constant interaction when integrating the theory learned in the classroom with the practice, increasing the student's interest, autonomy and knowledge. Conclusion: the use of active teaching methodologies and consequent evaluation through the assessment tool, online portfolio, contributes to increase the self-confidence, self-knowledge and reflective competence of students throughout the training process, in addition to providing theoretical and practical dialogue aimed at the profile of the professional that it aims to form.